Ejection fraction and blood pressure variabilities in acute myocardial infarction patients and its relationship with serum electrolytes - Sahar Mudassar, Mudassar Ali, Faheem Mahmood, Farukh Bashir, Shoaib Ahmed, Amna Mubeen, Amal Shaukat, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In patients with acute myocardial infarction, age, BMI, blood pressure, and electrolytes all influence ejection fraction improvement following percutaneous coronary intervention (PCI) . Many studies have looked into the long-term consequences of these factors, but none have found evidence that they have an impact on PCI efficacy. Aim: To evaluate the effectiveness of percutaneous coronary intervention (PCI) and predict prognosis in AMI patients by measuring blood pressure and serum electrolytes. Methods: It is a study that will last for a lengthy period of time. Before and after angioplasty, the EF of 40 patients with acute myocardial infarction (AMI) was measured in this research. The data were analysed using the SPSS 23 statistical package. Results:The effects of age (P = 0.34) and BMI (P = 0.49) on EF improvement are not well understood. The difference between those with initial high blood pressure and those without (P = 0.12), although not significantly different. Although serum calcium levels (P = 0.74) were normal, elevated sodium and potassium levels (P = 0.05) were shown to be associated with lower EF improvement. The concentrations of sodium and potassium in the blood were found to have a P value of 0.07. Conclusion: After PCI, patients with AMI have a better prognosis if they are older and have a normal BMI; nonetheless, greater blood sodium and potassium levels have a worse prognosis.